Olfactory Stimulation Modulates Visual Perception Without Training - Tsushima, Yoshiaki; Nishino, Yurie; Ando, Hiroshi (Frontiers in Neuroscience, 2021)
Considerable research shows that olfactory stimulations affect other modalities in high-level cognitive functions such as emotion. However, little known fact is that olfaction modulates low-level perception of other sensory modalities. Although some studies showed that olfaction had influenced on the other low-level perception, all of them required specific experiences like perceptual training. To test the possibility that olfaction modulates low-level perception without training, we conducted a series of psychophysical and neuroimaging experiments. From the results of a visual task in which participants reported the speed of moving dots, we found that participants perceived the slower motions with a lemon smell and the faster motions with a vanilla smell, without any specific training. In functional magnetic resonance imaging (fMRI) studies, brain activities in the visual cortices [V1 and human middle temporal area (hMT)] changed based on the type of olfactory stimulation. Our findings provide us with the first direct evidence that olfaction modulates low-level visual perception without training, thereby indicating that olfactory-visual effect is not an acquired behavior but an innate behavior. The present results show us with a new crossmodal effect between olfaction and vision, and bring a unique opportunity to reconsider some fundamental roles of olfactory function.